KAJIAN LITERATUR: TEORI BELAJAR KOGNITIF JEAN PIAGET DALAM PEMBELAJARAN IPS DI SEKOLAH DASAR - Sardi, Elis Tiara; Masayu, Nikita Oky; Triningsih, Triningsih; Marini, Arita; Yunus, Mahmud (Sindoro: Cendikia Pendidikan, 2024)
Social Studies education aims to help students understand social life through an interdisciplinary approach that includes subjects like history, geography, and economics. It also prepares students to actively participate in society. Piaget’s cognitive development theory, which emphasizes structured stages of thinking and learning through experience, is particularly relevant for elementary students aged 7-12. At this age, children move from concrete to formal operational thinking, allowing them to better process and organize information. By applying Piaget’s theory, Social Studies lessons can encourage critical thinking and meaningful understanding. Rather than focusing on memorization, students learn to analyze and connect concepts, such as understanding historical events in context. This approach helps them build deeper knowledge and essential analytical skills for active civic engagement.